Shtikat Haarchion . A Film Unfinished - Hersonski, Yael (Belfilms, 2010)
Verzio FF Duration: 01:30:00 A cinematic quest for the truth behind one of the most mysterious Nazi propaganda films, shot inside the Warsaw Ghetto in May 1942. A rough draft of a silent film juxtaposes meticulously staged scenes of Jews enjoying a life of luxury in the ghetto with chilling images that required no staging at all. Ironically, after the war, filmmakers and museums used bits and pieces from the film as objective, general illustrations of the narratives collected from survivors and written documents. Few people were aware of the cynical manner in which these images were created and invaluable witness they bear. The film interweaves diary entries written by ghetto inhabitants during the filming, the testimonies of living survivors, and the transcript of the interrogation of a German cameraman, testifying about his role in the making of the film. By juxtaposing the filmed scenes with their behind-the-scenes' layered reality, A Film Unfinished challenges the authenticity of archival images and the way the past is perceived.